Network Quality Measurements of LTE Drones - Woo Jwa, Jeong; Hie Won, Joong (International Journal of Engineering and Technology, 2018)
Cellular-connected drones can provide beyond line-of sight control (BVLOS), low latency, real time communication, robust security, and wide range coverage. Cellular-connected drones have several key potential applications in enhanced LTE and 5G networks. The objective of the study is to evaluate field measurement data collected during drone flights in the KT Long-Term Evolution (LTE) networks in Seoul and Jeju, Korea. The multicopter drones are developed with LTE modem and LTE test smart phone for field measurements. The radio network quality between drones and LTE base transceiver stations (BTS) is evaluated by measuring downlink metrics such as the serving cell RSRP, RSRQ, SINR, modulation types of downlink, the downlink and uplink throughputs, and LTE PUSCH Tx Power on reference signal. In the existing LTE networks, field measurements show that there is no problem in C&C of BVLOS operations in the flight height up to 150m but the data rate requirements for video transmission does not meet at high flight altitudes.Â Â